From Womb to Words: Unveiling the Changing Understanding of Hysteria - Teber, Sena (International Journal of Language and Literary Studies, 2024)
In ancient periods, there was the tendency to label a woman as mad or hysteric if she behaved in a strange manner. The reason was that, since at those times women were considered to be inferior creatures, their bodies were thought to be degraded easily. Accordingly, in the medieval period, hysteria was linked to distress in the womb, which would affect the whole body easily. In that sense, in this period hysteria was only associated with women. Especially ancient Greeks believed that hysteria occurred due to not having enough sex or orgasms. Therefore, according to them the cure for this ailment was getting married and having a satisfying sexual life. However, in the dark Middle Ages, hysteria started to be related to witchcraft, rather than sexual dissatisfaction. It was still linked to women only, but this time they were believed to be possessed by the Devil if they showed any disturbances or symptoms of hysteria. With the developments in science and technology, the understanding of hysteria changed from being associated with unfulfilled sexual drives or spirit possession to being a result of having psychological scars due to mental traumas or repressions. Accordingly, the purpose of this study is to reflect the changing understanding of hysteria through female characters from 20th century American drama.